Damping force in the transit-time method of optical stochastic cooling - Alexander Zholents (Physical Review Special Topics. Accelerators and Beams, 2012)
This brief note clarifies one specific aspect of a transient-time method of optical stochastic cooling that often creates confusion for the first time surveyor of this cooling technique.